40 Years of Hydrogen–Deuterium Exchange Adjacent to Heteroatoms: A Survey - Michelotti, Alessia; Roche, Maxime (Synthesis, 2019)
Deuteration of bioactive molecules is gaining more and more attention, especially after the approval of the first deuterated drug (Austedo™) by the US Food and Drug Administration (FDA). Not only is deuteration important for drug development, the amount of deuterium in a molecule is critical for the production of standards in mass spectrometry and the selectivity of the deuteration is mandatory for NMR applications. Very frequently, the molecules involved in these applications contain several heteroatoms. It has been demonstrated that oxygen-, nitrogen-, and more recently, sulfur-containing molecules can be easily deuterated at the α position leading to high deuterium incorporation. In this review we will focus our attention on the historical background and the recent progress made on heteroatom-directed deuteration, with particular attention on the catalysts and the mechanisms that drive such transformations.1 Introduction2 Oxygen-Directed Deuteration3 Nitrogen-Directed Deuteration4 Sulfur-Directed Deuteration5 Conclusion
Keywords: deuterium; deuterium labeling; hydrogen–deuterium exchange; deuteration; C–H activation